Non-binary Learning: a Series of Design Studios for an Ecofeminist Pedagogy - Noemí Gómez Lobo; Diego Martín Sánchez (Dearq)
Fostering diversity in schools of architecture and urban planning can be achieved not only by improving quotas and establishing much-needed positive actions, but also by preparing curricula, teaching methodologies and themes for learning about how to regenerate more just and inclusive environments that address the dual climate and social crises. The aim of a series of design studios run at different universities in Tokyo between 2020 and 2022 was to re-read the city and its architectures from a gender perspective that challenges binary assumptions and includes an awareness of the more-than-human. This article reviews the theoretical frameworks used in the studios to discuss how an ecofeminist pedagogy can establish cross-scale, multifunctional projects that challenge the assumption of division.